Genetic studies on performance traits of Jersey crossbred cows in sub-temperate region - R K TAGGAR; A K DAS; DHIRENDRA KUMAR; V MAHAJAN (Indian Journal of Animal Sciences, 2014)
The evaluation of production performance traits of Jersey crossbred cows is essential for their genetic improvement in sub-temperate region. The present investigation was conducted on 619 records of 265 Jersey crossbred cows maintained at an organized institutional dairy farm in North-West Himalayan state of Himachal Pradesh for 29 years (1981–2009). The production traits considered in the present study were 305day lactation milk yield, peak yield, lactation milk yield, lactation length, average milk yield/day of lactation length, average milk yield per day of calving interval. Heritability, genetic and phenotypic correlation coefficients were estimated for these traits. Periods showed significant effect while season had nonsignificant effect on these production traits. Parity had highly significant effect on all the traits except lactation length. These production traits showed significantly higher values in winter except peak yield. These traits did not show a consistent trend across different periods, which are due to change in managemental conditions. In third lactation these traits showed better performance. The heritability estimates of these traits were very low except of peak yield. The genetic associations among these traits were positive and high except association of lactation length with other traits which were negative and low. The phenotypic associations were observed low to high across these traits.